1980
DOI: 10.1073/pnas.77.9.5471
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged derangements of canine myocardial purine metabolism after a brief coronary artery occlusion not associated with anatomic evidence of necrosis

Abstract: Changes in myocardial purine metabolism were studied after temporary coronary artery occlusion and subsequent reperfusion in the dog. Sequential myocardial biopsies were performed to allow for measurements of ATP, adenine nucleotide, nucleoside, and base concentrations after 15 min of ischemia, and after 90 min and 72 hr of reperfusion following this period of ischemia. Control, nonischemic sites were also sampled. After 15 min of coronary occlusion, subendocardial ATP concentrations (reported in nmol/mg of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(73 citation statements)
references
References 22 publications
4
68
0
1
Order By: Relevance
“…At 72 hr after release of a 15-min coronary occlusion, the ATP concentration in reperfused previously ischemic myocardium was significantly reduced (by 22% of normal), the percentage of systolic shortening of reperfused left ventricular segments was reduced (by 42% ofnormal), and ultrastructural abnormalities were present, despite the absence of necrosis (1,3). However, it was not known whether these changes ever were reversed to normal after longer periods of reperfusion and, if so, what the time course of the recovery is.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…At 72 hr after release of a 15-min coronary occlusion, the ATP concentration in reperfused previously ischemic myocardium was significantly reduced (by 22% of normal), the percentage of systolic shortening of reperfused left ventricular segments was reduced (by 42% ofnormal), and ultrastructural abnormalities were present, despite the absence of necrosis (1,3). However, it was not known whether these changes ever were reversed to normal after longer periods of reperfusion and, if so, what the time course of the recovery is.…”
mentioning
confidence: 96%
“…Previous studies from this laboratory have shown that brief (15 min) coronary occlusions followed by reperfusion do not cause necrosis but do result in prolonged abnormalities in myocardial biochemistry, function, and ultrastructure (1)(2)(3). At 72 hr after release of a 15-min coronary occlusion, the ATP concentration in reperfused previously ischemic myocardium was significantly reduced (by 22% of normal), the percentage of systolic shortening of reperfused left ventricular segments was reduced (by 42% ofnormal), and ultrastructural abnormalities were present, despite the absence of necrosis (1,3).…”
mentioning
confidence: 99%
“…After 15 min of coronary occlusion, myocardial ATP concentration decreases substantially; it remains significantly depressed for many hours to days of reperfusion and usually returns to normal by 7 d (25,66,67). In other studies, creatine phosphate was shown also to fall markedly within minutes following coronary occlusion but to return to normal quite rapidly during coronary reperfusion.…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 99%
“…In addition to the prolonged postischemic left ventricular dysfunction outlined above, biochemical abnormalities persist following reperfusion (66,67). After 15 min of coronary occlusion, myocardial ATP concentration decreases substantially; it remains significantly depressed for many hours to days of reperfusion and usually returns to normal by 7 d (25,66,67).…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 99%
“…Based on experimental and clinical studies, the concepts of myocardial stunning [6][7][8][9][10] and hibernation [11][12][13] were developed and studied. Stunning refers to temporary depression of cardiac contraction following a bout of ischemia.…”
Section: Pathophysiologic Studiesmentioning
confidence: 99%